The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3168/jds.2020-18780
|View full text |Cite
|
Sign up to set email alerts
|

Fermented milk retains beneficial effects on skeletal muscle protein anabolism after processing by centrifugation and supernatant removal

Abstract: Lactobacillus-fermented milk can stimulate anabolic effects in skeletal muscle. Fermented milk containing Lactobacillus produces aqueous molecules, such as free AA and lactate. This study aimed to investigate how processing fermented milk by centrifugation and removal of supernatant affects AA absorption and postprandial skeletal muscle protein synthesis (MPS) when mice are fed fermented milk. We gavaged male Sprague-Dawley rats with skim milk (S), fermented milk (F), or processed fermented milk (P), and exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…As a result, we confirmed that MPS is lower not only after unfermented milk but also after acidified unfermented milk ingestion than after yogurt consumption over the entire measured time [69]. In addition, in a study using yogurt fermented by another lactic acid bacterium, postprandial MPS was increased by yogurt than the original unfermented milk, too [70]. Looking at these reports in more detail, the concentration of blood amino acids, such as leucine, was higher in fermented milk and acidified unfermented milk than in unfermented milk at 30 and 60 min after ingestion [69,70].…”
Section: Acute Effects Of Yogurt Ingestion On Skeletal Musclesupporting
confidence: 79%
See 2 more Smart Citations
“…As a result, we confirmed that MPS is lower not only after unfermented milk but also after acidified unfermented milk ingestion than after yogurt consumption over the entire measured time [69]. In addition, in a study using yogurt fermented by another lactic acid bacterium, postprandial MPS was increased by yogurt than the original unfermented milk, too [70]. Looking at these reports in more detail, the concentration of blood amino acids, such as leucine, was higher in fermented milk and acidified unfermented milk than in unfermented milk at 30 and 60 min after ingestion [69,70].…”
Section: Acute Effects Of Yogurt Ingestion On Skeletal Musclesupporting
confidence: 79%
“…On the other hand, proton pump inhibitors do not affect amino acid absorption after ingestion of acidified milk but reduce it after ingestion of fermented milk [69]. Casein protein may be more highly digestible by pepsin in fermented milk than in raw milk in the stomach [70]. These results indicate that casein protein in fermented milk is partially digested by lactic acid bacterial fermentation, potentially contributing to its reduced resistance to pepsin.…”
Section: Faster Rate Of Digestion/absorption Of Yogurt Protein Compar...mentioning
confidence: 96%
See 1 more Smart Citation
“…The high-quality amino acid pattern that yoghurt has therefore reduces energy intake by stimulating satiety and regulates blood sugar levels (Baspinar & Güldaş, 2021). Sumi et al (2021) found that fermented milk improved amino acid absorption and postprandial skeletal muscle protein synthesis, thus stimulating the anabolic action in skeletal muscle.…”
Section: Proteolysismentioning
confidence: 99%
“…Sumi et al. (2021) found that fermented milk improved amino acid absorption and postprandial skeletal muscle protein synthesis, thus stimulating the anabolic action in skeletal muscle.…”
Section: Fermented Milk and Lactic Acid Bacteria—first Look At Nutrit...mentioning
confidence: 99%